Croatia : Diagnostic Review of Consumer Protection and Financial Literacy, Volume 2. Comparison against Good Practices - World Bank (Washington, DC, 2014)
As financial markets develop and deepen, one of the key issues for a fair, open and efficient market is effective consumer protection and financial literacy. The European Union takes the approach that an effective regime of financial consumer protection should allow consumers to have access to: sufficient information to make informed decisions about their financial choices; cost-effective recourse mechanisms to redress violations of financial service contracts; and programs of consumer education and financial literacy that empower them to understand their financial rights and obligations. This review has found that the quality of consumer protection in financial services in Croatia has improved in recent years. In particular, the approval of the 2007 Consumer Protection Act incorporated many of the EU Directives related to financial consumer protection. In addition, the National Council on Consumer Protection was established in 2008 to advise the Government on its national strategy for consumer protection in the coming years. A nation-wide baseline survey of financial literacy would provide useful information in designing programs in financial education and consumer awareness. As pioneered in the United Kingdom, financial literacy surveys can identify which part of the population is most vulnerable to financial abuse. The baseline survey should be segmented by age, gender, geographic area, household income, and formal education. After a period of three to five years, a follow-up survey could be done to evaluate the effectiveness of the programs of financial education and consumer awareness.